Enhancing tourist experience through interactive speaking: A practical application of english communication skills at the tourist information centre in Banyuwangi - Rinda, Renata Kenanga; Finalia, Ratih; Indrastana, Nodistya Septian; Rahmanita, Meiga (Journal of English Language Teaching and Learning (JETLE), 2025)
This qualitative descriptive study investigates the application of English-speaking skills in authentic service encounters at the Tourist Information Centre (TIC) in Banyuwangi, East Java. Drawing on approximately 10 observed interactions with both domestic and international tourists—including visitors from Indonesia, Singapore, and Malaysia—the study identifies four key stages of communication: information delivery, feedback provision, negotiation, and agreement confirmation. These stages reveal the strategic use of clarification, turn-taking, and negotiation techniques in real-time exchanges. The findings suggest that effective and adaptive spoken English significantly contributes to improved service quality and tourist satisfaction. By analyzing how TIC staff engage in interactive speaking practices, this research highlights the practical importance of communicative competence in tourism settings and provides insights for English for Specific Purposes (ESP) education.